Understanding Podocyte Biology to Develop Novel Kidney Therapeutics - Lal, Mark A.; Patrakka, Jaakko (Frontiers in Endocrinology, 2018)
Over the past two decades it has become increasing clear that injury and loss of podocytes is an early and common clinical observation presented in many forms of glomerulopathy and chronic kidney disease. Identification of disease-causing monogenic mutations in numerous podocyte-expressed genes as well as studies conducted using preclinical animal models have shown that the podocyte plays a central role in establishing kidney dysfunction. In this review, we summarize current knowledge regarding the potential for podocyte-targeted therapies and give our view on how a deeper understanding of the molecular makeup of the podocyte will enable future therapeutic interventions. Specifically, we recount some of the currently described podocentric strategies for therapy and summarize the status and evolution of various model systems used to facilitate our understanding of the molecular and functional underpinnings of podocyte biology.